Impact of MPOWER tobacco control policies on smoking prevalence and issues of illicit cigarette trade - Bui, Wency Kher Thinng (2019)
Smoking is one of the significant public health threats and killing about six million people annually. Therefore, World Health Organization (WHO) introduced the Framework Convention on Tobacco Control (FCTC) since 2003, then later, WHO released the package of six MPOWER measure to assist the country with the implementation of the tobacco control policies. Malaysia officially joined with FCTC in 2005 and improved the Control for Tobacco Products Regulation according to the MPOWER measures in 2008. However, only 0.3% reduction on Malaysian smoking prevalence between the year 2011 and 2015 and such small reduction has become a major concern among the policy-makers to achieve the two targets; non-communicable disease (NCD) voluntary target (15% by 2025) and End-Game target (less than 5% by 2045). Besides, the elimination of illicit cigarette trade is also a concern by policymakers., Therefore, surveillance is indeed to combat the illicit cigarette trade, but these are underground activities and unlikely to get recorded. Yet, the industry-involved studies showed that Malaysia has high illicit cigarette market share, but these studies have been claimed that always exaggerate the incidence of illicit cigarettes. Thus, the tobacco industry also argued that high retail price caused by taxation creates incentives for illicit trade. However, many studies have proven that their arguments are invalid. This study conducted three analysis for three research objectives. First, Abridge SimSmoke model was employed and accompanied by the reinforcement of non-price tobacco policies and taxation; the cigarette retail price is simulated to at least increased from RM16.20 to RM22.05 to achieve the NCD target. However, for the End-Game target, the cigarette retail price is required to be increased to at least RM40.40. Secondly, this study obtained cigarette consumption and sales data from government agencies and conducted the discrepancy method to measure the size of illicit cigarettes in Malaysia. In 2015, 7,718.8 million sticks of illicit cigarettes were consumed and generated at least RM2,161.3 million loss of excise tax revenues. Also, the measure of illicit cigarette market share was exaggerated by the tobacco-involved studies where they are more likely to understate the legal sales data and create a higher rate of illicit market share. Lastly, a panel data analysis of 61 countries for nine years was estimated using the system generalized-method-of-moments estimators. The results diverge from the tobacco industry claims since high retail price does not increase the illicit cigarette trade. The country with better governance can further mitigate illicit problems. Therefore, it requires substantial implementation of tobacco control by the governments and intense enforcement strategy to reduce illicit cigarettes trade. From all the findings, the Malaysian Government should consistently increase tobacco taxation to achieve the targets since the price indicator is not a significant factor in driving the illicit cigarette trade. Instead, enforcing a better governance quality in addressing the problem of illicit cigarette trade. These efforts would potentially reduce the smoking prevalence and smoking-attributable deaths in Malaysia and able to achieve the targets, hence combat the illicit cigarette trade problem.